THE ROLE OF TIKTOK APPLICATION TO LEARN ENGLISH VOCABULARY: A SURVEY ON STUDENT TEACHERS - Anggi Wanda Venalinda; Muhamad Laudy Armanda (IAIN Syekh Nurjati Cirebon, 2023)
English has four skills that must be mastered in the field of education. To master these four skills, it is necessary to comprehend English vocabulary. Due to the fact that student teachers as future teachers belong to Gen Z and primary and secondary students nowadays are classified as Gen Alpha, the TikTok application is currently quite popular with them. The widespread availability of social media with massive opportunities to provide major roles in current society. Therefore, this study aims to survey student teachers' perceptions of using the TikTok application to learn and teach English vocabulary. This study employed descriptive qualitative, which was analyzed by using descriptive statistics. The data was gathered through a questionnaire that was given to 90 student teachers at one of the universities in Indonesia. The researchers also distributed a semi-structured interview to several participants. According to the data, it was indicated that the majority of students have a favorable perspective toward the TikTok app and believe it can help them to learn English. In addition, they were expected to use it to teach vocabulary in the English class. Thus, it is suggested that student teachers as future teachers maximize the advantages of the TikTok application as a learning tool, which enables to improve of the planning of training programs.